2019
DOI: 10.1097/nna.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Changing New Graduate Nurse Profiles and Retention Recommendations for Nurse Leaders

Abstract: OBJECTIVE This study compares and contrasts new graduate nurse attributes and perceptions using findings from a 2010 study and a recent analysis of new graduate nurses participating in the same residency program. BACKGROUND As millennials saturate the healthcare work environment, their unique views and needs will influence the evolution of new graduate nurse residencies. METHODS This study used previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…The findings regarding rewards were consistent with the literature which showed that verbal and written praise were highly valued by millennials and contribute to motivation and satisfaction (Tyndell, Scott, Jones, & Cook, 2019). This desire for frequent positive feedback parallels millennials’ measures of ‘likes’ and ‘views’ in social media (Kosterlitz & Lewis, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The findings regarding rewards were consistent with the literature which showed that verbal and written praise were highly valued by millennials and contribute to motivation and satisfaction (Tyndell, Scott, Jones, & Cook, 2019). This desire for frequent positive feedback parallels millennials’ measures of ‘likes’ and ‘views’ in social media (Kosterlitz & Lewis, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to improving the nursing curriculum and hiring practices in LTC, RNs would benefit from additional supports to assimilate to the charge nurse role. Tyndall et al () made several suggestions to improve new graduate RNs integration into LTCFs. Recommendations include peer support and one‐on‐one meetings to develop peer and supervisory relationships, the provision of career ladder programs, and directing tuition assistance to leadership and gerontological courses that are important to improving new graduate integration, while acquiring the knowledge, skill and judgement for competent decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies about the experience of being a charge nurse in LTCF from the perspective of RNs in this role, and they have focused on singular aspects of their role, such as their supervisory role (McGilton et al, ; Prentice et al, ) or factors that influence their intent to stay (Kuo, Lin, & Li, ; Tyndall, Scott, Jones, & Cook, ). Current literature has discussed nursing supervision and leadership in LTC without discussing the specificities of the RN in the charge nurse role.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies endeavour how to intervene, rather than whom to support. According to a systematic review , interventions to reduce nursing turnover mainly focus on newly graduated nurses (Ten Hoeve et al, 2020;Tyndall et al, 2019) but less address to hold employed staffs, especially those with advanced degree.…”
Section: Introductionmentioning
confidence: 99%